Analysis of Science Literacy Learning with Scientific Inquiry Approach in Increasing Science Competence of Students - Basam, Fajri; Rusilowati, Ani; Ridlo, Saiful (Universitas Negeri Semarang, 2017)
This study aims to describe the implementation of learning, to analyze the effectiveness of learning, students' competency science profile, and teacher and student responses toward science literacy learning with scientific inquiry approach. The research method used is Mix Method with concurrent embedded model of quantitative method become primary with research subjects are science teachers and students of class VII SMPN 1 Lilirilau and MTs DDI Pattojo Soppeng Regency, South Celebes Province. The results shows that (1) the implementation of learning is very good with 86% the average percentage of implementation. (2) The effectiveness of learning is shown on student's learning completeness classically that is 90% of students reach KKM value. These results have reached the established criteria of 75%. The average increase in students' science competence is 0.69 in the medium category. The students' competency profile based on PISA criteria appears dominant in the explanation of scientific phenomena, whereas based on the criteria of science literacy dominant in science as the body of knowledge. (4) The teacher's response toward scientific literacy learning was positive with an average score of 3.83, and (5) students' responses toward scientific literacy learning are quite positive with an average score of 3.22 out of a maximum score of 4.00.